Tenth International Conference on Computer Modeling and Simulation (Uksim 2008) 2008
DOI: 10.1109/uksim.2008.73
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Reduction Models Approach Using Neural Network

Abstract: Simulation is often used for the evaluation of a Master Production Schedule (MPS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The selected studies exploring the economic profits of optimal decision-making processes can be generally divided into three groups: production efficiency improvement [16], [18], [19], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [20], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], energy cost savings [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], and space savings [53], [56], [82], [83], [84], [85], [86],…”
Section: ) Economic Profitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected studies exploring the economic profits of optimal decision-making processes can be generally divided into three groups: production efficiency improvement [16], [18], [19], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [20], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], energy cost savings [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], and space savings [53], [56], [82], [83], [84], [85], [86],…”
Section: ) Economic Profitsmentioning
confidence: 99%
“…Environmental footprint reduction [16], [18], [19], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [20], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70] [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81] [53], [56], [82], [83], [84], [85], [86], [87] [99], [100], [101], [102],…”
Section: Manufacturing Waste Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The learning of the network is supervised, so it is necessary to divide the database into learning and validation data sets. Previous work [8,10] using the OBS algorithm has shown that 24 hidden neurons are sufficient for modeling the system, so the initial network structure uses 25 hidden neurons. The initial learning is therefore carried out with a neural network comprising 10 inputs, 25 hidden neurons, and one output (i.e., 301 parameters), for a maximum of 50,000 iterations.…”
Section: Database and Initialmentioning
confidence: 99%
“…Neural networks can extract performing models from experimental data [9]. Consequently, the use of neural networks has been proposed in order to reduce simulation models [8][9][10]. To build a neural model, an important issue is determining the structure of the network.…”
Section: Introductionmentioning
confidence: 99%